Makna Modernitas bagi Seniman Seni Rupa Modern Indonesia - Iwan Pirous (Antropologi Indonesia, 2000)
In this article, the author assumes that the clear-cut distinction between modern and traditional arts is merely a form of scientific construction which needs to be re-examined. The political, social and cultural problems underlying the development of modern art, in particular in developing countries are quite different from those in Euro-American countries. Therefore, the artistic expressions are also different and cannot be analyzed in terms of aesthetical standard as developed in the West. The author provides evidences that the modern art in Indonesia has its own discourse. An intensive dialogue' between the traditional and the modern elements is going on. Three cases drawn from three artists are discussed in this article as the example of the ongoing dialogue.